2003
DOI: 10.1088/0022-3727/36/3/201
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and application of holographic Bragg gratings in lithium niobate channel waveguides

Abstract: Permanent refractive-index gratings in waveguide devices are of high potential for optical communication systems that make use of the high spectral selectivity of holographic filters, e.g. dense wavelength division multiplexing (DWDM), optical sensors, or narrow-bandwidth mirrors for integrated waveguide lasers. In this contribution we review our results on holographically recorded refractive-index gratings in Cu-doped LiNbO 3 channel waveguides. Elementary holograms are recorded with green light and read in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 49 publications
0
101
0
2
Order By: Relevance
“…( ) is the strength of the nonlinearity that varies along the direction. In optics, spatially inhomogeneous nonlinearities can be realized by using inhomogeneous doping [5,6]. If is replaced by time , Eq.…”
Section: Exact Solutions For Bright and Dark Solitonsmentioning
confidence: 99%
“…( ) is the strength of the nonlinearity that varies along the direction. In optics, spatially inhomogeneous nonlinearities can be realized by using inhomogeneous doping [5,6]. If is replaced by time , Eq.…”
Section: Exact Solutions For Bright and Dark Solitonsmentioning
confidence: 99%
“…Note as well that such a demultiplexer can be also built on the basis of dynamic holographic grating recorded in a PR crystal (Hukriede, et al, 2003;Petrov, et al, 2001;Petrov, et al, 2003;Runde, et al, 2005). The scheme of such photorefractive band-drop filter proposed in (Petrov, et al, 2003) is shown in Fig.…”
Section: Spectral Multiplexing Of Dynamic Hologramsmentioning
confidence: 99%
“…For this purpose, experimental parameters of the waveguide fabrication process are thickness of the evaporated titanium film, width of the lithographically patterned titanium stripes, and in-diffusion conditions (diffusion temperature T and time ). With these values the two-dimensional diffusion profiles T ( , ) of titanium are calculated using literature data for the diffusion constant and index change ∆ ( T ) [15]. Then the wave equation is solved numerically for the resulting index profile ∆ ( , ) by utilizing a finite difference method, resulting in the mode dispersion and the field distributions E( ) of the guided modes propagating in the -direction.…”
Section: Modeling Of the Directional Couplermentioning
confidence: 99%
“…Alternatively, we have shown that holographic recording of elementary gratings using two-beam interference is an appropriate and efficient technique to record narrowband reflection gratings using the photorefractive effect in LiNbO 3 [14,15]. Compared to other optical materials like glasses or polymers, a multiplexer of the described scheme in LiNbO 3 allows for additional fast electrical switching of the Bragg grating in the GHz regime due to the superior electro-optic properties of this substrate material.…”
Section: Introductionmentioning
confidence: 99%